Does the Fatigue Induced by a 30-Minute Run Affect the Lower Limb Acceleration Spikes’ Asymmetries? - Gabriel Delgado-García; Isabel M. Martín-López; Fulgencio Soto-Méndez; Arturo Quílez-Maimón; Salvador Boned-Gómez (Bioengineering)
Running-induced fatigue affects several biomechanical parameters, and yet few studies are focused on the acceleration spikes’ asymmetries. This study aimed to evaluate the effects of a 30 min run on lower limbs spikes’ asymmetries. Eighteen recreational runners (35.6 ± 7.5 years; seven women) performed a treadmill running protocol at a moderate speed and acceleration spikes’ asymmetries and kinematic (temporal) parameters were measured via accelerometers—on the tibias and sacrum—and photogrammetry. Acceleration spikes’ parameters were continuously measured and averaged per minute to assess the relationship between fatigue and acceleration spike asymmetries via a linear regression model. Right tibial acceleration spikes increased over time (r = 0.9; p < 0.001) and left tibia spikes decreased (r = 0.78; p < 0.001), with a rise in tibial load asymmetry from 9% to 25% at the end (r = 0.98; p < 0.001). This study suggest that fatigue affects the acceleration spikes of the two legs differently, with increasingly greater acceleration spikes in the right (dominant) leg. These findings should be considered, as greater asymmetries are related to overuse injuries and lower efficiency. Also, in studies focusing on running mechanics with fatigue, it is recommended that researchers collect data from both limbs, and not only from the right (dominant) leg.